(untitled) (Journal of Atomic and Molecular Sciences, 2011)
The first two-dimensional potential energy surface for the Ne-BeH van der Waals interaction is calculated by the single and double excitation coupled-cluster theory with noniterative treatment of triple excitations [CCSD(T)]. Mixed basis sets, aug-cc-pVQZ for the Be, H and Ne atom, with an additional (3s3p2d1f1g) set of midbond functions are used. There is a single global minimum at R_e=6.95 a_0 and θ_e=72.5^° with well depth -34.43607 cm^-1. Based on the potential, the rovibrational energy level structure of the Ne-BeH complex is also investigated.